Effect of soil type and level of seismicity on seismic design of reinforced concrete school building - Hanis Athirah, Roslan (2019)
Seismic considerations are not taken into account for design and construction in Malaysia. but after the incident happened on 5th June 2015, earthquake of 6.0 magnitudes had struck in Ranau, Sabah, which lasted for 30 seconds. After the incident happened, the local authority starts to reconsider to implement the seismic design especially school building. In Malaysia, reinforced concrete (RC) school buildings will be the main focus of the community's protection when there is a catastrophic disaster to remain until the disaster is reduced. Therefore, it is very important to ensure that RC school building design in the future will be able to accommodate the burden of the earthquake, which means that the RC school building will work even after the earthquake. The objective of the study is to determine the effect of different Soil Type and effect of Level of Seismicity on the amount of steel reinforcement. The model use for the study is four-storey RC school building which is design based on Eurocode 8. There are total of ten models with different Soil Type and Level of Seismicity. Then, the analysis is conducted to all of the models by using Tekla Structural Designer to obtain both of the objectives. The information based on the amount of steel required is provided from the analysis. It is represented by using Design Response Spectrum graph and tabulated tables that contained information like bending moment. Based on the results, the percentage different of weight of steel reinforcement required for non-seismic design which considering Soil Type is increased 38%, 92% and 131% for Soil Type A, Soil Type C and Soil Type E, respectively. Thus, it can be concluded that model built on Soil Type E required high amount of steel reinforcement per 1m³ concrete. While for different magnitude of PGA, the results show that the percentage difference of steel reinforcement required compared to non-seismic design for beam and column of the whole building had increased from 13%, 66% and 131% for PGA equals to 0.04g, 0.07g, and 0.10g respectively. Thus, it can be concluded that model built on PGA of 0.10g required high amount of steel reinforcement per 1m³ concrete Therefore, Soil Type and Level of Seismicity should be taken into consideration for design since these variables influence the amount of steel used.